Réponses

Meilleure réponse !
2014-03-11T20:37:22+01:00

Enlever les parenthèses et réduire:

a= 3a + 5 - (2a + 7) + (8 - 5a)

a= 3a + 5 - 2a - 7 + 8 - 5a

a= 3a - 2a - 5a + 5 - 7 + 8

a= -6a + 6


b= -b + 4 + (3b - 2) - (8b - 5)

b= -b + 4 +  3b - 2 - 8b + 5

b= -b + 3b - 8b + 4 - 2 + 5

b= -6b + 7


c= 6 - 5c + 3c - (4 - 6c) + 5 + (7 - 2c)

c= 6 - 5c + 3c - 4 + 6c + 5 + 7 - 2c

c= -5c + 3c + 6c - 2c + 6 - 4 + 5 + 7

c= 2c + 14


d= d- 1 - (3d + 4) + (5 - 4d) - (7d + 5) + 5

d= d - 1 - 3d - 4 + 5 - 4d - 7d - 5 + 5

d= d - 3d - 4d - 7d - 1 - 4 + 5 - 5 + 5

d= -13d + 0

d= -13d



merci beaucoup
Je t'en prie ^^
Il me semble que la a) est fausse...
a= 3a + 5 - (2a + 7) + (8 - 5a)

a= 3a + 5 - 2a - 7 + 8 - 5a

a= 3a - 2a - 5a + 5 - 7 + 8
a= -4a + 6
  • Utilisateur Brainly
2014-03-11T20:40:35+01:00
Réduction: A) 3a + 5 - (2a+7) + (8-5a) 3a +5 -2a -7 +8 -5a -4a +6 B) -b +4 +(3b -2) -(8b-5) -b +4 +3b -2 -8b +5 -6b +7 C) 6-5c +3c - (4-6c) +5 + (7-2c) 6 -2c -4+6c +5 +7 -2c 2c +14 D) d-1-(3d+4) + (5-4d) -(7d+5)+5 d-1-3d-4 +5 -4d -7d -5 +5 -13d Voilà! J'espère t'avoir aidé(e) ! :)